Adherence to weekly iron folic acid supplementation and associated factors among adolescent girls – A mixed-method study - Nisha Maheswari Y.; Sunitha Kandasamy; Ezhil Ramya J.; Padmavathi Subbiah; Prathiksha D. Davidson; Muthukrishnan Gopal; Lakshmi K. Velappan; Shantaraman Kalyanaraman (Journal of Family Medicine and Primary Care, 2024)
Context: Despite the Weekly Iron folic acid supplementation (WIFS) program, the prevalence of anaemia among adolescent girls remains high. Phase 1 Indian Council of Medical Research (ICMR) task force study conducted in 2016 in Kallur showed that the IFA provision rate for adolescent girls was 72% but the consumption rate was only 15% in the Kallur area. The present study was done to identify the gaps for the difference between provision and consumption rate of weekly IFA tablets among adolescent girls using the WHO conceptual framework in home-based settings. Materials and Methods: This crosssectional study with a mixedmethod design was conducted from October 2020 to December 2021. Quantitative data were collected from 972 adolescent girls and their parents using a structured pretested questionnaire, whereas qualitative exploration was done by focus group discussions. Descriptive analysis and bivariate analysis were used to analyse the quantitative data. Qualitative data were analysed and integrated with quantitative results. Results: The overall number of girls who were aware of Iron Folic acid therapy (IFAT) was 704 (72%). However, only 132 (13%) adolescent girls were found to be adherent to IFA therapy. Multivariable regression analysis revealed that side effects encountered on intake of IFAT (Odds ratio (OR) =0.5, P = 0.009) were associated with higher rates of nonadherence, whereas regular supply (OR = 13.6, P = 0.000), health education to parents (OR = 2.76, P = 0.002), and experiencing benefits (OR = 1.72, P = 0.006) were associated with higher rates of adherence. These were substantiated by qualitative findings. Conclusions: Ignorance on the impact of anaemia on adolescent health, fear of side effects, unpleasant effects experienced on intake of Iron folic acid (IFA), and inadequate counselling determines the adherence to weekly IFA supplements among adolescent girls.